Introduction of the Digital Gaming Relationship - Sokka, Miikka (2025)
In recent decades, there has been a growing interest in studying the appeal of digital games. However, there is still a call for further research, especially on the theoretical and methodological advancements. Hence, a novel approach and a concept of the Digital Gaming Relationship (DGR) is presented. The DGR model is adapted from earlier work on physical activity and with the central concept as “meaning,” it provides an alternative perspective to motivation-oriented literature for the field of game studies. With this approach, the fundamental view is that each person has a varying relationship with digital games and gaming over their life span. The relationship builds on the individual’s encounters with the social world of digital gaming and its cultural meanings. In the long term, accruing digital gaming-related knowledge, experiences, and emotional connections contributes to a rich tapestry of meaning, thus creating a deep and meaningful relationship capable of shaping one’s actions, behaviors, and even identity. The framework theorizes the mechanisms of an individual’s socialization process to the digital gaming world and illustrates that the relationship with digital games includes much more than just playing them. In this article, the theoretical roots and key concepts of the DGR are introduced, and the practical applicability of the approach is discussed.